Assessment of the frequency of sperm annulus defects in a large cohort of patients presenting asthenozoospermia. Issue 1 (December 2015) - Dirami, Thassadite; Rode, Baptiste; Wolf, Jean-Philippe; Gacon, Gérard; Dulioust, Emmanuel; Touré, Aminata
Abstract Background The annulus is a ring-shaped structure located beneath the plasma membrane that connects the midpiece and the principal piece of mammalian sperm flagellum. It has been suggested that the annulus acts as a morphological organizer, guiding flagellum assembly during spermiogenesis, and as a diffusion barrier, confining proteins to distinct compartments of the flagellum in mature sperm. Previous studies on small cohorts of patients have attempted to correlate annulus defects with the occurrence of human asthenozoospermia. An absence of the annulus has been shown to be frequently associated with asthenozoospermia. Findings We tried to obtain a more precise estimate of the frequency of annulus defects, by screening a large cohort of 254 men presenting asthenozoospermia (mean progressive motility of 24 %) by the immunodetection of SLC26A8, a transmembrane protein that has been shown to be specifically localized to the annulus. By contrast to previous reports, our results indicate that annulus defects are associated with asthenozoospermia in only 1.2 % of cases. Conclusions We conclude that defects or an absence of the annulus are not frequently associated with asthenozoospermia. The use of annulus defects as a diagnostic endpoint in patients is therefore not appropriate. Resume Introduction L'annulus (Anneau de Jensen) est localisé à la jonction de la pièce intermédiaire et de la pièce principale du flagelle des spermatozoïdes de mammifères. Sa fonction reste encore mal établie mais il est suggéré qu'il puisse être essentiel à l'assemblage du flagelle et à la compartimentation des protéines le long du flagelle. Des études précédentes réalisées sur des petites cohortes de sujets asthénozoospermiques ont mis en évidence des défauts fréquents de l'annulus sur les spermatozoïdes de ces sujets. Resultats Afin de mieux estimer la fréquence des défauts de l'annulus chez les sujets asthénozoospermiques, nous avons analysé une cohorte de 254 sujets asthénozoospermiques (mobilité moyenne 24 %) par immunodétection de l'annulus, en utilisant un anticorps spécifique de la protéine SLC26A8, un constituant établi de l'annulus. Nos résultats indiquent que les défauts ou absence de l'annulus ne sont retrouvés qu'à une fréquence de 1.2 %. Conclusions A partir de cette étude réalisée sur le plus grand effectif de sujets asthénozoospermiques à ce jour, nous pouvons conclure que les défauts ou l'absence d'annulus ne sont pas fréquemment associés à l'asthénozoospermie modérée; l'utilisation de l'annulus comme outil de diagnostic de ce type d'asthénozoospermies, comme initialement suggéré, ne nous semble donc pas applicable.